-3=x-5/7

Simple and best practice solution for -3=x-5/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=x-5/7 equation:



-3=x-5/7
We move all terms to the left:
-3-(x-5/7)=0
We add all the numbers together, and all the variables
-(+x-5/7)-3=0
We get rid of parentheses
-x-3+5/7=0
We multiply all the terms by the denominator
-x*7+5-3*7=0
We add all the numbers together, and all the variables
-x*7-16=0
Wy multiply elements
-7x-16=0
We move all terms containing x to the left, all other terms to the right
-7x=16
x=16/-7
x=-2+2/7

See similar equations:

| 70=28-14x | | 12a+4a*4a+9=0 | | 1/3x+1/4x=2x-17 | | 6y−3=6y+8 | | 42x+158=1166 | | 8x^2-48x=-135 | | 6y+5+5Y+7=15y-20 | | 129=3(8+5p) | | 2x/3=12/9 | | 4(v-2)=28 | | 17y=119 | | 3(4t-4)=10t1=7+2t | | x/4-8=-13 | | 8x2+2x-6=0 | | 5(2/5x-3)=4x+15 | | 6-7(6-6n)=-3n+9 | | (2x+1)/100=x | | (x+42)+2x=90 | | 5-8(a-3)=93 | | n=15÷-3 | | 5k=8(k+3) | | 9-2(5x+4)=6-4(3x+7)+2x | | 4-6x=-x-6x | | 6x+7=4×-5 | | -35+5x=6(x-5) | | 510=8x | | 2x-4=31-3x | | 3(x+2)+4x-5=7(x+1-6 | | 7x+6=3(5x-4)-10 | | 9x-5+4x=7×+43-2x | | -5m-2(m-3)=-8-m+4 | | 2(-8n-13/8)=-525/4 |

Equations solver categories